The relationship between computed tomography‐derived body composition, systemic inflammatory response, and survival in patients undergoing surgery for colorectal cancer. Issue 1 (20th November 2018) - Dolan, Ross D.; Almasaudi, Arwa S.; Dieu, Ly B.; Horgan, Paul G.; McSorley, Stephen T.; McMillan, Donald C.
Abstract: Introduction: Colorectal cancer is the fourth leading cause of cancer mortality in developed countries. There is evidence supporting a disproportionate loss of skeletal muscle as an independent prognostic factor. The importance of the systemic inflammatory response as a unifying mechanism for specific loss of skeletal muscle mass in patients with cancer is increasingly recognized. The aim of the present study was to delineate the relationship between the systemic inflammatory response, skeletal muscle index (SMI), skeletal muscle density (SMD), and overall survival in patients with colorectal cancer. Materials and methods: The study included 650 patients with primary operable colorectal cancer. Computed tomography scans were used to define the presence of visceral obesity, sarcopenia (low SMI), and myosteatosis (low SMD). Tumour and patient characteristics were recorded. Survival analysis was carried out using univariate and multivariate Cox regression. Results: A total of 650 patients (354 men and 296 women) were included. The majority of patients were over 65 years of age (64%) and overweight or obese (68%). On univariate survival analysis, age, ASA, TNM stage, modified Glasgow Prognostic Score (mGPS), body mass index, subcutaneous fat index, visceral obesity, SMI, and SMD were significantly associated with overall survival (all P < 0.05). A low SMI and SMD were significantly associated with an elevated mGPS (<0.05). On multivariate analysis, SMI (Martin) [hazard ratio (HR) 1.50, 95% confidence interval (CI) 1.04–2.18, P = 0.031], SMD (Xiao) (HR 1.42, 95% CI 0.98–2.05, P = 0.061), and mGPS (HR 1.44, 95% CI 1.15–1.79, P = 0.001) were independently associated with overall survival. SMD but not SMI was significantly associated with ASA ( P < 0.001). Conclusions: This study delineates the relationship between the loss of quantity and quality of skeletal muscle mass, the systemic inflammatory response, and survival in patients with operable colorectal cancer.